فاعلية برنامج تدريبي في تنمية إدراك الاتجاه وإدراك المكان لذوي الإعاقة البصرية دراسة شبه تجريبية في مدرسة ذوي الإعاقة البصرية في مدينة حلب - ريا منال (Latakia University Journal -Medical Sciences Series, 2018)
هدفت الدراسة التعرف إلى فاعلية تنمية إدراك الاتجاه وإدراك المكان في تعلم المهارات الحركية الأساسية لذوي الإعاقة البصرية. وأجريت الدراسة على عينة عمدية قوامها (16) تلميذا وتلميذة من مدرسة المكفوفين في مدينة حلب، وقد قسمت العينة إلى مجموعتين متساويتين الأولى ضابطة والمجموعة الثانية تجريبية عدد كل منهما (8) تلاميذ. وتم تطبيق اختبارات بدنية واختبارات إدراك الاتجاه وإدراك المكان لقياس التلاميذ. وأشارت نتائج الدراسة إلى وجود فروق معنوية ذات دلالة إحصائية لصالح المجموعة التجريبة للمعاقين بصريا. وتوصي الباحثة بضرورة تنمية إدراك الاتجاه وإدراك المكان في تعلم المهارات الأساسية لذوي الإعاقة البصرية. This research aims to learn about the effectiveness of developing perception of both direction and space in order to learn fundamen tal movement skills for People with visual disability. This study was conducted on agroup of (16) students (male & female) from a school for the blind school, and this group had been devided into two equal groups, first of them is standard and the the second one is experimental each one has (8) students. Physical and perception of both direction and space tasks had been implemented to evaluate the students. The results of the study showed that there are significant differences with statistical indication in favor of the experimental group of People with visual disabilities . The Researcher recommends on the necessity of developing perception of both direction and space in order to learn basic kinetic skillsfor People with visual disabilities.